Personal finance management application for university students - Ng, Sian Hong (2022)
Personal finance management is very important for everyone in this world, especially for university students. By definition, personal finance management not only focuses and involves the handling of investments but is also used to keep track of transactions and to do budgeting. University students have to learn about how to manage their money carefully since they are almost working adults and need to learn to become independent. In addition, each of the transactions records involves a different situation and location. Therefore, it is not easy to keep track of the transactions. Despite this, most university students manage their personal finance by memorizing the transactions using their brains. Obviously, this is not an effective way to handle personal finance management. Currently, there are several personal finance applications in the market that are used to help people manage personal finance. However, most of them are fairly complicated and hard to grasp, especially when dealing with interest rates and loans. In fact, university students are better off without the involvement of interest rates and loans as they are more likely to only keep track of transactions and perform budgeting transactions. Therefore, the personal finance applications that are currently available in the market are limited to specific aspects of personal finance and thus, are not suitable for university students. The objective of this project is to address the problems above by developing a useful and secure desktop-based personal finance management application. This application allows users to maintain and keep track of their personal finance such as to manage incomes and expenses as well as to do budgeting to avoid unnecessary transactions finance. Lastly, clear, and easy user interfaces are provided to reduces the complexity involved in managing their personal finance.